PENGARUH FRAUD DIAMOND DALAM MENDETEKSI FINANCIAL STATEMENT FRAUD (Studi Empiris pada Perusahaan Ritel yang Terdaftar di Bursa Efek Indonesia Tahun 2014 – 2016) - Djoko Kristianto, Pypyt Tunjungsari, Dewi Saptantinah Puji Astuti & (Universitas Slamet Riyadi, 2018)
The purpose of this research is analyzing financial performance retail company listed on the indonesian stock (BEI) years 2014 - 2016 reviewed taking financial stability, external pressure, financial target, nature of industry and rationalization. The research is a case study in the new company retail to 2014 - 2016 who are enrolled in bei. Was used in the study samples from 18 company with by means of a method of sampling the sampling method of purposive. An instrument of analysis that was used in this research was simple linear regression analysis. The results of the study obtained the conclusion that: (1) a variable financial stability has not been affecting the financial statement fraud (2) a variable external pressure it has some positive effects to financial statement fraud (3) a variable financial target can have negative effects to financial statement fraud (4) a variable nature of industry influence to financial statement significant fraud (5) a variable rationalization influential in a negative way significant fraud to financial statement.Keywords: financial stability, external pressure, variable financial target, nature of industry, rationalization, financial statement fraud